EFFECT OF HYDROPONIC MAIZE FODDER ON HEMATOLOGY AND SERUM BIOCHEMISTRY OF WEANER RABBITS - Jatutu, S. S.; Muhammad, A. S.; Egbo, M. L.; Bello. K. M.; Tijjani, B. M.; Muazu, M. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This study investigated the effects of replacing conventional concentrate feed with hydroponic maize fodder on the hematological and serum biochemical parameters of weaner rabbits. Forty weaner rabbits were randomly assigned to five treatments: T1 (100% concentrate), T2 (75% concentrate + 25% hydroponic maize fodder), T3 (50% concentrate + 50% hydroponic maize fodder), T4 (25% concentrate + 75% hydroponic maize fodder), and T5 (100% hydroponic maize fodder) in a Completely Randomize Design (CRD). The experiment lasted for six weeks. Blood samples were collected at the end of the trial for hematological and serum biochemical analysis. Results showed no significant differences (p>0.05) in hematological parameters (PCV, Hb, WBC, RBC, MCV, MCH, MCHC, platelets, neutrophils, and lymphocytes) and serum biochemical parameters (total protein, glucose, albumin, urea, cholesterol, and total bilirubin) across all treatments. These findings suggest that hydroponic maize fodder can partially or fully replace conventional concentrate in weaner rabbit diets without adversely affecting their hematological and serum biochemical profiles.